Chimeric Antigen Receptor T-Cells in B-Acute Lymphoblastic Leukemia: State of the Art and Future Directions - Greenbaum, Uri; Mahadeo, Kris Michael; Kebriaei, Partow; Shpall, Elizabeth J.; Saini, Neeraj Y. (Frontiers in Oncology, 2020)
Use of adoptive T-cell therapy modified with chimeric antigen receptor (CAR-T) has revolutionized treatment of patients with relapsed/refractory (r/r) B-cell acute lymphoblastic leukemia(B-ALL). CAR-modified T-cells directed against CD19 antigen have produced response rates as high as 90% in clinical trials for r/r B-ALL. Despite high rates of complete remissions, the durability of responses has been poor with frequent relapses, especially in adult B-ALL population. Systemic toxicities from CAR T-cell therapy and standardization of toxicities grading and management is another major hurdle in the developing CAR-T field. In this review, we discuss the latest evidence of CAR-T therapy in B-ALL, potential mechanisms of relapse and barriers to CAR-T cell therapy in B-ALL. We also debate on the role of allogeneic hematopoietic stem cell transplant (allo-HCT) post CAR-T therapy.